Предмет: Математика,
автор: 1КиТ7
Преобразуйте в многочлен: а) 4(m-n)²+4m(m-n)
Ответы
Автор ответа:
0
4(m²-2mn+n²)+4m²-4mn=4m²-8mn+4n²+4m²-4mn=8m²-12mn+4n²
Автор ответа:
0
= 4 (m² - 2·m·n+ n² ) + 4 m² - 4m·n =
= 4 m² - 8 m n + 4 n² + 4 m²- 4 m n =
= 8 m ² - 12 m n + 4 n ²
= 4 m² - 8 m n + 4 n² + 4 m²- 4 m n =
= 8 m ² - 12 m n + 4 n ²
Похожие вопросы
Предмет: Математика,
автор: manasbekovaisida
Предмет: Українська мова,
автор: alinaalbul2306
Предмет: Окружающий мир,
автор: Plshelp2230
Предмет: Математика,
автор: mnlahnst